IMPROVING THE AVAILABILITY OF MANUFACTURABILITY INFORMATION THROUGH DECENTRALIZATION OF PROCESS PLANNING - Opiyo, Eliab Z. (Tanzania Journal of Engineering and Technology, 2018)
Process planning is part of the general product development and production process that usually follows design and precedes manufacturing. Manufacturability and process planning information in general play central role in many product development and production activities, including paradoxically, conceptual and detail design - the activities that take place before process planning. The need of conducting some of the process planning activities formally before or during design is thus rather obvious. One of the main research issues is therefore the identification of the process planning activities that can be performed before the traditional process planning phase and handling of the process planning information so as to adequately provide the designers with the manufacturability information needed during conceptual and detail design. Another issue is how to support collaboration during process planning and how to maintain continuity of the process planning tasks. This paper suggests the decentralization of the process planning task and proposes the execution of the process planning activities in a piecemeal fashion, starting right after receiving an order and specifying the requirements for a product. Process planning under the proposed procedure consists of six semi-autonomous sub-phases, some of which comprise activities that must be conducted prior to the process planning phase. This helps to overcome the problem of timely availability of manufacturability information during the execution of upstream and downstream product development and production activities. The paper also proposes a computer-based method of handling the manufacturability information generated in various stages of the product development and production process. A database design and structure of prototype software that manages the process planning information are presented and discussed. Furthermore, a case study conducted to explore how the proposed process planning procedure could be put in use is presented and discussed.